The relationship between motivation and job satisfaction and organizational commitment among the non-commissioned officers of the police force: a preliminary study in Melaka / Rozalli Hashim, Arshad Hashim and Saladin Mohd Rasool - Hashim, Rozalli; Hashim, Arshad; Mohd Rasool, Saladin (Unit Penyelidikan dan Perundingan, 2003)
This study was conducted to examine the relationship between demographic constructs of the police NCO's, their motivation and job satisfaction and organizational commitment with data obtained from 80 personnel from the stat of Melaka. the study has found out that all demographic constructs were insignificantly correlated to all of the ten Kovach motivational factors. it was found that different forms of job satisfiers (positive listed items) and dissatisfies (negative listed items) are significant at P<0.00 implying that the police personnel was generally satisfied with their job. Contingency coefficients revealed that a few of the demographic variables were correlated with the organizational commitment attributes at P<0.05. The result implies that in general, the police personnel are highly committed to their profession. Two model equations of organizational commitment (positive) and non-organizational commitment (negative) of the police personnel proved that while the police personnel is highly committed and satisfied with their job, better wages and chances of being promoted are the two factors that can contribute to job dissatisfaction especially among younger personnel.